Two New Species of Simulium (Nevermannia) (Diptera: Simuliidae) from Northern Thailand - Hiroyuki Takaoka (2018)
Two new species of black flies, Simulium (Nevermannia) fruticosum sp. nov. and S. (N.) chiangklangense sp. nov. are described on the basis of samples collected in northern Thailand. These new species are assigned to the feuerborni species-group of the subgenus Simulium (Nevermannia), and are easily distinguished from S. (N.) feuerborni Edwards, the only species of the same group known thus far in Thailand, by their simple cocoon without any anterodorsal projection. © 2005, Japanese Society of Tropical Medicine. All rights reserved.